Community vertical stratification drives temporal taxonomic and phylogenetic beta diversity in a mixed broadleaf-conifer forest - Chai, Pengtao; Xie, Jiajie; Yang, Lisheng; Zheng, Rong; Bian, Yuxuan; Fu, Jiaqin; Wang, Yunquan; Chen, Jianhua (Frontiers in Ecology and Evolution, 2023)
Temporal change of β diversity provides a better understanding of the extent and consequences of species composition in forest communities as the ongoing global climate change. However, relatively little is known about how temporal β diversity change across vertical stratifications in forest. Here we divided more than 5,000 tree individuals from a mixed broadleaf-conifer forest into four vertical stratifications (i.e., shrub, subcanopy, lower canopy, upper canopy) to quantify how vertical stratifications drive temporal change of taxonomic and phylogenetic β diversity. We found that taxonomic β diversity significantly decreased while phylogenetic β diversity showed an insignificant increase after five years. When considering vertical stratifications, taxonomic β diversity in both subcanopy, lower canopy and upper canopy significantly changed with inconsistent directions, but phylogenetic β diversity in shrub significantly increased. Moreover, the significant decrease in taxonomic β diversity mainly driven by changes of species compositions in shrub and subcanopy stratifications (with 85.89% contributions). The changes in phylogenetic β diversity driven by the shifts in the shrub and upper canopy (with 96.02% contributions). Our study suggests that taking community vertical stratifications into consideration contributes to a better understanding of temporal β diversity in forest communities.